2015
DOI: 10.1371/journal.pone.0120228
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose Intravenous Vitamin C Combined with Cytotoxic Chemotherapy in Patients with Advanced Cancer: A Phase I-II Clinical Trial

Abstract: BackgroundBiological and some clinical evidence suggest that high-dose intravenous vitamin C (IVC) could increase the effectiveness of cancer chemotherapy. IVC is widely used by integrative and complementary cancer therapists, but rigorous data are lacking as to its safety and which cancers and chemotherapy regimens would be the most promising to investigate in detail.Methods and FindingsWe carried out a phase I-II safety, tolerability, pharmacokinetic and efficacy trial of IVC combined with chemotherapy in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
106
0
11

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(124 citation statements)
references
References 51 publications
7
106
0
11
Order By: Relevance
“…The role of ascorbic acid (commonly known as Vitamin C) in cancer is extremely controversial [2023]. Many investigators have found that ascorbic acid is highly toxic to tumor cells and combinations of ascorbic acid with several anticancer drugs are more than additive in tumor cell killing [19, 2426], while other investigators have found no effect in cell culture and animal models [27, 28].…”
Section: Introductionmentioning
confidence: 99%
“…The role of ascorbic acid (commonly known as Vitamin C) in cancer is extremely controversial [2023]. Many investigators have found that ascorbic acid is highly toxic to tumor cells and combinations of ascorbic acid with several anticancer drugs are more than additive in tumor cell killing [19, 2426], while other investigators have found no effect in cell culture and animal models [27, 28].…”
Section: Introductionmentioning
confidence: 99%
“…A more recent phase I-II. clinical study by Hoffer et al [77] reported transient (lasting for 3-13 months) stable disease in 3 out of the 16 patients in the study. Actually all the existing group studies have failed to provide evidence for a benefit in hard clinical endpoints such as survival.…”
Section: High Dose Intravenous Vitamin C (Ivc) Therapy In Cancermentioning
confidence: 75%
“…In recent days, there is an increased interest in studying Vitamin C as an adjunct treatment with chemotherapy (Hoffer et al, 2015;Fritz et al, 2014). Some studies have explored that Vitamin C Induced Ascorbate radical produces hydrogen peroxide which is toxic towards Cancer cells (Jacobs et al, 2015;Stephenson et al, 2013 (Raza et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Several strategies are being researched to block NIK to block activation of NF-ĸB (Carcamo et al, 2002). Several clinical studies have been conducted in order to assess the safety of high dose Vitamin C in cancer patients and it was found that high dose Vitamin C is safe in majority of patients if the right protocol is used (Hoffer et al, 2015). 363 Raza et al…”
Section: Discussionmentioning
confidence: 99%